2004
DOI: 10.1002/chem.200305714
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of the Hydrogen Transfer from the OH Group to Oxygen‐Centered Radicals: Proton‐Coupled Electron‐Transfer versus Radical Hydrogen Abstraction

Abstract: High-level ab initio electronic structure calculations have been carried out with respect to the intermolecular hydrogen-transfer reaction HCOOH+.OH-->HCOO.+H(2)O and the intramolecular hydrogen-transfer reaction .OOCH2OH-->HOOCH(2)O.. In both cases we found that the hydrogen atom transfer can take place via two different transition structures. The lowest energy transition structure involves a proton transfer coupled to an electron transfer from the ROH species to the radical, whereas the higher energy transit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
88
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(105 citation statements)
references
References 77 publications
15
88
2
Order By: Relevance
“…[29] This fact was later explained because the acidic hydrogen is abstracted through a proton-coupled electron transfer mechanism. [30,31] The complete details of the reaction mechanism of reactions 1-3 are given elsewhere [30] and Scheme 1 shows their pictorial representation. Reaction (1) can occur in two different ways, namely through a proton-coupled electron transfer mechanism (pcet, Scheme 1 a) or through a hydrogen atom transfer process (hat, Scheme 1 b).…”
mentioning
confidence: 99%
“…[29] This fact was later explained because the acidic hydrogen is abstracted through a proton-coupled electron transfer mechanism. [30,31] The complete details of the reaction mechanism of reactions 1-3 are given elsewhere [30] and Scheme 1 shows their pictorial representation. Reaction (1) can occur in two different ways, namely through a proton-coupled electron transfer mechanism (pcet, Scheme 1 a) or through a hydrogen atom transfer process (hat, Scheme 1 b).…”
mentioning
confidence: 99%
“…This interpretation of the HOMO and HOMO-1 was consistent with the PCET picture, except they are fully occupied, which is indicative of the protons and electrons transferred to different acceptor (CO 2 ) sites. [63][64][65] Analysis of the spin density, visualized in Fig. 4, demonstrated that it was concentrated at first on the boron atom (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The above results revealed that there were some other factors influencing the reaction besides the redox potential of quinone. The process of electron transfer between p-BQ and NHPI should be a proton-coupled electron transfer (PCET) process because the energy of the transition structure of PCET is lower than that of the conventional radical hydrogen atom abstraction mechanism [15][16][17]. In this pathway, NHPI interacted with quinone to give a hydrogen-bond complex, and then electron proton transfer occurred.…”
Section: Catalytic Activity Of Substituted Benzoquinone In Ethylbenzementioning
confidence: 98%